2018
DOI: 10.14302/issn.2578-8590.ipj-17-1910
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Stiffness Influences the Time Dependence of CTGF Protein Expression in Müller Cells

Abstract: Following ocular trauma and retinal detachment, gliotic changes in the retina may develop over the subsequent month, a process known as PVR (proliferative vitreoretinopathy). There have been no successful therapeutic interventions to inhibit PVR. The protein CTGF (Connective Tissue Growth Factor) has been associated with retinal PVR and other fibrotic diseases of the retina in clinical studies but the mechanistic link between different pathologies and retinal gliosis has not been determined. In addition, CTGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Given the fact that, in our study, TGF-β1 secretion was unaltered and an increase in DCN secretion was observed, it was not surprising that no change in CTGF secretion was found in response to increasing stiffness. CTGF has also been reported to be downstream of YAP, and we reported there was more YAP retention in the cytoplasm potentially contributing to less upregulation in response to the stiffer environment (Davis and Foster, 2018;Shome et al, 2020). In addition, there was downregulation of CTGF gene expression in response to stiffer hydrogels confirming the findings that protein secretion was unaltered.…”
Section: Discussionsupporting
confidence: 82%
“…Given the fact that, in our study, TGF-β1 secretion was unaltered and an increase in DCN secretion was observed, it was not surprising that no change in CTGF secretion was found in response to increasing stiffness. CTGF has also been reported to be downstream of YAP, and we reported there was more YAP retention in the cytoplasm potentially contributing to less upregulation in response to the stiffer environment (Davis and Foster, 2018;Shome et al, 2020). In addition, there was downregulation of CTGF gene expression in response to stiffer hydrogels confirming the findings that protein secretion was unaltered.…”
Section: Discussionsupporting
confidence: 82%
“…Given the fact that, in our study, TGF-β1 secretion was unaltered and an increase in DCN secretion was observed, it was not surprising that no change in CTGF secretion was found in response to stiffness. CTGF has also been reported to be downstream of YAP, and we reported there was more YAP retention in the cytoplasm potentially contributing to less upregulation in response to the stiff environment (66,67). In addition, there was downregulation of CTGF gene expression in response to stiff hydrogels confirming the findings that protein secretion was unaltered.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, changes in YAP/ TAZ localization and CTGF protein expression in Müller cells may contribute to the development of PVR/retinal gliosis during retinal detachment. 72 These findings reveal how the Hippo pathway and other signalling pathways interact to contribute to PVR development. Thus, targeting YAP/TAZ activity may be a potential therapy to slow the progression of PVR.…”
Section: Immunohistochemical Analysis Of Vegfr2 and Yap In Human Pvrmentioning
confidence: 87%